Sosialisasi Literasi Digital Dan Tuturan Cyberbullying Yang Berdampak Hukum Kepada Para Pelajar Di Kota Mataram - Syahid, Agus; Rahmatyar, Ana; Pribadi, Teguh Iman; Setiawan, Muhamad Alam; Putri, Tiara Resta (CV. Global Cendekia Inti, 2024)
The use of internet and social media in Indonesia has become more extensive in recent years. It enables everyone to interact, share, and participate with fellow internet users. Social media has a positive and negative impact, one of the negative impact is cyberbullying. Cyberbullying has been defined as any form of aggressive communication using information and technology to mock others through social media. The content of the message is basically psychological violence or social terror. Digital literacy activities are an important step to avoid the act of cyberbullying. Seeing the importance of this activity, the service team carried out this activity with students in Mataram city namely SMA 1 Mataram. The service team focuses on introducing digital literacy and knowing cyberbullying phenomenon and how to prevent cyberbullying through sharing sessions activities. This activity was attended by 30 participants. The result of this community service show that students have awareness of the dangers of cyberbullying and the legal impacts from this action.